TRANSLATION CHARACTERISTICS OF LINGUISTIC AND PEDAGOGICAL TERMINOLOGY IN UZBEK AND ENGLISH ACADEMIC TEXTS (American Journal of Pedagogical and Educational Research, 2026)
The translation of linguistic and pedagogical terminology plays an important role in ensuring effective academic communication between languages and cultures. This study examines the translation characteristics of linguistic and pedagogical terms in Uzbek and English academic texts. The research purposes to identify major translation strategies, semantic challenges, and linguistic differences that impact the accuracy and clarity of translated terminology. Using qualitative comparative analysis, several academic texts in the fields of linguistics and pedagogy were analyzed. The findings demonstrate that terminological equivalence, contextual adaptation, and cultural specificity are the main factors affecting translation quality. The study also reveals that direct translation is not always sufficient because many pedagogical and linguistic concepts contain culture-bound meanings. The article highlights the importance of professional competence, contextual understanding, and terminological consistency in academic translation.